Pembelajaran Kewirausahaan Dengan Pendekatan Modul Berbasis Project Based Learning Dalam Eko-Sistem Bisnis Untuk Peningkatan Kemampuan Perancangan Bisnis Mahasiswa - Yulhendri Yulhendri; Nita Sofia; Sri Arita; Luqman Hakim; Nora Susanti; Wyanet Putri Alisha; Irma Irma; Delvia Safitri; Rosi Avrisa (Universitas Negeri Padang, 2022)
Entrepreneurship learning is a very important lesson for prospective economics teachers, because one of the competencies that must be possessed is to guide students so that they have life skills after completing their study. The learning is carried out in an Entrepreneurship practice course. Before they practice they must understand the business ecosystem as one of the prerequisites for the sustainability of a business. As long as these students carry out entrepreneurial practices, they are only business activities that are usually carried out by the general public without having innovation value and paying attention to coaching aspects. In this Action Research study, it was carried out by paying attention to where in stage 1, students showed low entrepreneurial interest, but by implementing Project-based learning with a business Ecosystem approach it was able to increase student interest in entrepreneurship and also increase student knowledge and understanding in maintaining sustainability business.